SCHIZOPHRENIA FOUND IN JERRY HICKFANG’S CHARACTER IN “THE VOICES” MOVIE - Asriwanti, Era; Surya, Satyawati; Setyowati, Ririn (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
The Voices movie is analyzed in this study because it is based on true story and also lots of lesson in life found in it such as, mental illness, behaves, and communicate. This research aimed at identifying the types of hallucination and the types of language abnormalities as reflected in the schizophrenic conversations of Jerry Hickfang's character in The Voices movie. The method used by the researcher is descriptive qualitative. The data of this study were analyzed by using Veague’s theory about hallucination and using Liddle et al (2002) theory about language abnormalities. In the process of analyzing all of those data, the researcher had some procedures namely watching the movie for several times, reading the movie script, then analyzing Jerry Hickfang’s character related to behaviour and language. The researcher mentioned two findings, they are types of hallucination and language abnormalities. For the types of hallucination, there are 3 types of hallucination stated in this movie, namely auditory hallucination, visual hallucination and olfactory hallucination. For the types of language abnormalities, there are 2 types of it stated in this movie, namely disorganization and dysregulation. In disorganization, there are 3 subtypes, namely looseness, peculiar use of word and non- logical reasoning (peculiar logic). In dysregulation, there are 2 subtypes namely perseveration and distractibility. There are 4 data of both (hallucination and language abnormalities).